PERFORMANCE OF RICE (Oryza sativa L.) CULTIVARS AT VARIOUS SPACINGS DURING KHARIF SEASON UNDER SOUTHERN ODISHA CONDITION - SUBIR RANA,; TRIPTESH MONDAL,; TANMOY SHANKAR,; TUFLEUDDIN BISWAS, (The Journal of Research ANGRAU, 2025)
A field experiment was conducted during Kharif, 2023 in split plot design with three replications. Results inferred that out of rice cultivars, V1-Naveen recorded highest plant height (113.3 cm), no. of tillers m-2 (292.1) and dry matter accumulation at harvest (1229.4 g m-2). No. of panicles m-2 (207.7), length of panicle (25.7 cm), total no. of spikelets panicle-1 (146.0), no. of filled grains panicle-1 (125.6) and 1000-grain weight (21.4 g) than other two cultivars. Naveen recorded significantly higher grain yield (5.2 t ha-1) than other cultivars due to the achievement of best results of all the yield attributing characters. The spacing of 15 cm × 15 cm recorded the highest plant height at harvest (106.9 cm). Similarly, the significantly higher no. of tillers m-2 at 60 DAT (266.4) than other spacings due to lesser competition in utilization of available nutrients as compared to closer spacings and maximum dry matter accumulation at harvest (1094.2 g m-2) were obtained with 15 cm × 15 cm spacing. The maximum panicle length (23.1 cm), total no. of spikelets panicle-1 (135.8), no. of filled grains panicle-1 (120.7) and grain yield (4.7 t ha-1) were recorded with 15 cm × 15 cm spacing which were significantly higher than other spacing options. Highest panicle length (26.1 cm), number of filled grains panicle-1 (128.7) and grain yield (5.5 t ha1) were recorded when Naveen cultivar was transplanted at 15 cm × 15 cm spacing which was significantly higher than all other combinations